2019
DOI: 10.5812/aapm.81785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxemia in the Determination of Short-Term Prognosis of Coronary Artery Bypass Graft Patients: A Prospective Study

Abstract: Background Respiratory failure and hypoxemia are the known complications of anesthesia and surgery. As a major surgery mainly at advanced ages, the coronary artery bypass graft (CABG) surgery could lead to hypoxemia in the early post-operative phase. Currently, the fraction of partial pressure of arterial oxygen to the fraction of inspired oxygen (PiO 2 /FiO 2 ) is used to determine the severity of the respiratory assault. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The process of weaning the patients from mechanical ventilation is of utmost importance for CABG patients (Elgebaly & Sabry, 2018) since the long‐term use of mechanical ventilation may not only increase the healthcare costs, but also may result in various adverse outcomes (Borges et al, 2017; Burns et al, 2019). There is a strong correlation between “intubation time” and “postoperative bleeding, readmission to the operating room, congestive heart failure, cardiac arrest, and hypotension” after the patient's condition has stabilized (Yousefshahi, Samadi, Paknejad, Bastan Hagh, & Aminzadeh, 2019). Hence, the reduction of intubation time would lead to reduced complications (Goodwin, Bissett, Mason, Kates, & Weber, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of weaning the patients from mechanical ventilation is of utmost importance for CABG patients (Elgebaly & Sabry, 2018) since the long‐term use of mechanical ventilation may not only increase the healthcare costs, but also may result in various adverse outcomes (Borges et al, 2017; Burns et al, 2019). There is a strong correlation between “intubation time” and “postoperative bleeding, readmission to the operating room, congestive heart failure, cardiac arrest, and hypotension” after the patient's condition has stabilized (Yousefshahi, Samadi, Paknejad, Bastan Hagh, & Aminzadeh, 2019). Hence, the reduction of intubation time would lead to reduced complications (Goodwin, Bissett, Mason, Kates, & Weber, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong correlation between "intubation time" and "postoperative bleeding, readmission to the operating room, congestive heart failure, cardiac arrest, and hypotension" after the patient's condition has stabilized (Yousefshahi, Samadi, Paknejad, Bastan Hagh, & Aminzadeh, 2019). Hence, the reduction of intubation time would lead to reduced complications (Goodwin, Bissett, Mason, Kates, & Weber, 1999).…”
mentioning
confidence: 99%
“…In the pathogenesis of delirium and other neurological consequences of cardiac and vascular surgery, many factors can be distinguished, including systemic inflammation and blood-oxygenation disorders [18,38,39]. Both of these factors occur in COPD patients, which may contribute to an increased incidence of delirium in this population.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis of 20 clinical cases including 3000 patients who received ASA as secondary cardiovascular prevention indicated that "aspirin resistance" in 28% of the patients correlated with a four-fold risk of CVD (20,21). ASA can be prescribed in numerous cardiovascular issues, including coronary artery bypass surgery (22)(23)(24)(25)(26), venous thrombosis, peripheral arterial disease, and cerebrovascular diseases (27)(28)(29).…”
Section: Cardiovascular Related Beneficial Effectsmentioning
confidence: 99%